The Influence of Service Strategies on Increasing the Number of Visitors in the Freshwater World Taman Mini Indonesia Indah - Galih Pangestu; Ayi Supriatna (Indo-Fintech Intellectuals: Journal of Economics and Business, 2022)
The purpose of this study was to understand how much influence service strategies have on the increasing number of visitors in the freshwater world of TMII. The research method used is quantitative method. The basis of this research is the survey method, which is the distribution of questionnaires to visitors about matters related to research in the Freshwater World of Taman Mini Indonesia Indah. The conclusion of this study is the result of interpretation of the effect of service strategies on increasing the number of visitors in the Freshwater World of Taman Mini Indonesia Indah is 0.78679 which falls into the strong category, then calculated in this study by 12.61 and t table by 1.984467 at error rate of 5 percent, which is where the hypothesis in this study is Ho rejected and Ha accepted, Then the coefficient of determination in this study is 60 percent. The advice that can be given to the Freshwater World of Taman Mini Indonesia Indah is to further improve services, the addition of facilities and infrastructure and the addition of freshwater biota collections